Mechanism for correlation in a coherent electron beam. (22nd January 2019) - Kodama, Tetsuji; Osakabe, Nobuyuki
Abstract : The correlation of electron counts from two detectors illuminated by a coherent beam is analyzed by associating the path of electrons with the Coulomb interaction between two electrons. The calculations reveal that the correlation can be caused by the collision between the accelerated electron and the electron before its acceleration. Abstract: The correlation of electron counts from two detectors illuminated by a coherent electron beam is analyzed by associating the path of the electron beam through the lenses with the direct Coulomb interaction between two individual electrons. This is shown to lead to a full statistical description of the electron counts. The dominant contribution to the correlation is found to be due to the trajectory displacement caused by the repulsive Coulomb interaction between the first anode and the cathode tip, and the correlation of electron counts is found to depend on the amount of defocusing on the shift of the virtual source for two electrons within the correlation time. The Coulomb scatterings, which altered the direction of two neighbor electrons, occur during the acceleration, leading to a significant decrease in the electron density. The Coulomb potential with no screening will then cause large-angle scattering of nearest-neighbor electrons within the correlation time. These results are consistent with those obtained by a previous experiment.